2009
DOI: 10.1074/jbc.m109.036079
|View full text |Cite
|
Sign up to set email alerts
|

Novel Roles of GATA1 in Regulation of Angiogenic Factor AGGF1 and Endothelial Cell Function

Abstract: AGGF1 is an angiogenic factor, and its deregulation is associated with a vascular malformation consistent with KlippelTrenaunay syndrome (KTS). This study defines the molecular mechanism for transcriptional regulation of AGGF1 expression. Transcription of AGGF1 starts at two nearby sites, ؊367 and ؊364 bp upstream of the translation start site. Analyses of 5-and 3-serial promoter deletions defined the core promoter/regulatory elements, including two repressor sites (from ؊1971 to ؊3990 and from ؊7521 to ؊8391,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 46 publications
2
62
1
1
Order By: Relevance
“…A high expression of VEGF in PMF megakaryocytes was seen also in an earlier study [18]. AGGF1 is reported to be under transcriptional control of GATA1 [14]. AGGF1 staining was positive in 91 % of XLTT megakaryocytes, compared to 100% in controls and PMF (Fig.…”
Section: Growth Factors In Megakaryocytessupporting
confidence: 51%
See 2 more Smart Citations
“…A high expression of VEGF in PMF megakaryocytes was seen also in an earlier study [18]. AGGF1 is reported to be under transcriptional control of GATA1 [14]. AGGF1 staining was positive in 91 % of XLTT megakaryocytes, compared to 100% in controls and PMF (Fig.…”
Section: Growth Factors In Megakaryocytessupporting
confidence: 51%
“…Low staining of VEGF and AGGF1 in XLTT BM may relate to observations (available for VEGF via www.sabiosciences.com) that the promoter regions of their genes contain binding sites for GATA1 [14]. However, it is not clear if a transcription deficit accounts for their lower protein contents in XLTT because posttranscriptional mechanisms may also be of importance.…”
Section: Growth Factors In Megakaryocytesmentioning
confidence: 93%
See 1 more Smart Citation
“…The data in this study and in other reported publications27, 30, 33, 37 suggest that there is a receptor for AGGF1. The receptor for AGGF1 has not been reported yet and we are actively pursuing it.…”
Section: Discussionsupporting
confidence: 83%
“…Plasmids, transfection, and reporter assay FLAG-tagged Aggf1, Ccl2 promoter-luciferase construct, and NF-κB/p65 expression construct have been described previously [14][15][16][17][18] . Transient transfections were performed with Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA).…”
Section: Cell Culturementioning
confidence: 99%